Pengaruh Kualitas Produk, Citra Merek dan Persepsi Harga Terhadap Loyalitas Pelanggan Melalui Kepuasan Pelanggan Produk Nitrea PT. Pupuk Kujang Cikampek di Karawang - Purwanto, Dian; Hardini, Resti (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This study aims to analyze the influence of product quality, brand image, and price perception on customer loyalty with customer satisfaction as a mediating variable for the Nitrea urea fertilizer product of PT. Pupuk Kujang Cikampek in Karawang. This research uses a quantitative method by collecting data through questionnaires distributed to 133 respondents who have used the Nitrea urea fertilizer product. The data obtained were analyzed using the Structural Equation Modeling (SEM) method with the help of SmartPLS software. The results of the study indicate that product quality, brand image, and price perception have a positive and significant effect on customer satisfaction. In addition, product quality, brand image, and customer satisfaction also have a positive and significant effect on customer loyalty. However, price perception does not have a direct significant effect on customer loyalty but has a significant effect through customer satisfaction as a mediating variable. The conclusion of this study is that to increase customer loyalty, PT. Pupuk Kujang Cikampek needs to focus on improving product quality, strengthening brand image, and setting competitive prices that align with the benefits received by customers. Customer satisfaction is proven to be an important mediating variable in strengthening the influence of product quality, brand image, and price perception on customer loyalty.